Thermal, UV and FTIR Spectroscopic Studies of Mercury Cinnamate - Madhurambal, G.; Ravindran, B.; Mariappan, M. (Asian Journal of Chemistry, 2010)
A single crystal of mercury cinnamate was grown by slow evaporation of methanol solution at room temperature. The effect of mercury on the electronic structure of cinnamic acid was studied. In this research many miscellaneous analytical methods were used: infrared (FT-IR), UV and TG-DTA. The spectroscopic studies lead to conclusions containing the distribution of the electronic charge in molecule, the delocalization of p-electrons and the reactivity of metal complexes.